Epoxidations and Hydroperoxidations of α,β-Unsaturated Ketones An Approach through Asymmetric Organocatalysis - Reisinger, Corinna (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2012)
Corinna Reisinger has developed a new organocatalytic asymmetric epoxidation of cyclic and acyclic α,β-unsaturated ketones. In this thesis, Corinna documents her methodology, using primary amine salts as catalysts, and hydrogen peroxide as an inexpensive and environmentally benign oxidant. She describes the unprecedented and powerful catalytic asymmetric hydroperoxidation of α,β-enones, a process which produces optically active five-membered cyclic peroxyhemiketals in a single operation. She also proves the versatility and synthetic value of the cyclic peroxyhemiketals by converting them into highly enantioenriched acyclic and cyclic aldol products. Currently, these cyclic aldol products are inaccessible by any other synthetic means. Furthermore, cyclic peroxyhemiketals are precursors to optically active 1,2-dioxolanes which are of biological relevance. This work is a breakthrough in the field of asymmetric epoxidation chemistry and outlines the most efficient method in the literature for generating highly enantioselective cyclic epoxyketones known to date.